Netrin Synergizes Signaling and Adhesion through DCC. Issue 1 (January 2020) - Meijers, Rob; Smock, Robert G.; Zhang, Yan; Wang, Jia-Huai
Abstract : Netrin is a prototypical axon guidance cue. Structural studies have revealed how netrin interacts with the deleted in colorectal cancer (DCC) receptor, other receptors, and co-factors for signaling. Recently, genetic studies suggested that netrin is involved in neuronal haptotaxis, which requires a reversible adhesion process. Structural data indicate that netrin can also mediate trans -adhesion between apposing cells decorated with its receptors on the condition that the auxiliary guidance cue draxin is present. Here, we propose that netrin is involved in conditional adhesion, a reversible and localized process that can contribute to cell adhesion and migration. We suggest that netrin-mediated adhesion and signaling are linked, and that local environmental factors in the ventricular zone, the floor plate, or other tissues coordinate its function. Highlights: Structural studies reveal molecular details of netrin-mediated clustering of DCC and uncoordinated 5 (UNC5), suggesting how they switch between growth cone attraction and repulsion in axon guidance. Three separate DCC-binding sites have been identified on netrin, and each site can be targeted by competing receptors or cofactors. Environmental cofactors may affect netrin-mediated signaling and adhesion. Structural studies suggest that the auxiliary guidance cue draxin locally expressed in the spinal cord alters netrin–DCC interactions to promote adhesion and axonal fasciculation. We propose that netrin mediates conditional adhesion between cells decorated with netrin receptors. Conditional adhesion is a reversible and highly localized process that can facilitate fasciculation, haptotaxis, and downstream signaling.